2023
DOI: 10.37934/araset.29.2.268275
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Smart Farming Technology Among Rice Farmers

Abstract: Application of smart farming technology in rice farming activity is relevant in facing the challenges in achieving food security and improving the wellbeing of farmers. In Malaysia, food security is synonymous with the adequacy of rice domestic supply for the Malaysian population. Therefore, to achieve the target set in Sustainable Development Goal 2 which is to achieve zero hunger, the rice sector needs to be more competitive by encouraging farmers to utilize modern technology. Smart farming is an emerging co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Finally, Zaman et al. (2023) reported that interviewed Malaysian farmers were generally positive toward using smart farming technologies. However, the current usage is still limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Zaman et al. (2023) reported that interviewed Malaysian farmers were generally positive toward using smart farming technologies. However, the current usage is still limited.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to Pivoto et al (2018), the adoption of livestock smart farming technologies in Brazil is still low, while technologies for crop production (e.g., UAVs) are used more often. Finally, Zaman et al (2023) reported that interviewed Malaysian farmers were generally positive toward using smart farming technologies. However, the current usage is still limited.…”
Section: Study Descriptions and Farmers' Adoption Or Intention To Ado...mentioning
confidence: 99%
“…To guarantee that the prototype system's output will match the study's purpose, the DFD (Data flow) and ERD (Entity-relationship) diagrams were created [12]. Additionally, it will make clear the crucial conditions for the data, database, module, and functioning of the prototype system.…”
Section: Methodsmentioning
confidence: 99%
“…It emphasizes the need for economic analysis and improved farmer education to support effective adoption. (NBK Zaman, 2023) A key component of Agriculture 4.0, precision agriculture makes use of cutting-edge technology like big data, IoT, AI, GPS, and drones to increase agricultural output while reducing environmental impact. The adoption of sustainable farming techniques is impeded by various challenges such as interoperability of systems, adoption costs, and data management, which calls for the implementation of education and training initiatives.…”
Section: S International Journal Of Arts Science and Humanitiesmentioning
confidence: 99%